Menuju Kesetaraan dalam Beragama yang Berbudaya: Refleksi Seminari Injili - Togardo Siburian (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: This article discusses a variety of modern man who is more civilized from the Evangelical perspective. Nowadays, the relations between different religious people is still filled with religious violence and conflicts. This happens because of extreme radicalism views wich perhaps are caused by the leftovers of our religious studies and practices in the past. There was a misunderstanding in processing religion wich could destroy the future of human civilization due to the absence of a culture of togetherness. The Evangelical Christianity may participate to think few principles of religious life wich are better for present humanity. The recommended principles are: 1) the importance of natural religious comparison in the normal society, 2) returning to the principle of missional church, 3) prioritizing the ethical emphasis more than the apologetical, 4) the balance between faith commitment and religious tolerance, 5) prophetic leadership rather than priesthood only, 6) faith particularism than religious exclusivism in inter-religious approach, 7) personal spirituality rather than individual religiosity. Thereby it is hoped that religious people may live together easier within the context of national unity and world peace. KEYWORDS: religious, conflict, collective civilization, normal comparison, ethical, prophetic, missional, particular.